2011
DOI: 10.1093/infdis/jir303
|View full text |Cite
|
Sign up to set email alerts
|

Ceestatin, a Novel Small Molecule Inhibitor of Hepatitis C Virus Replication, Inhibits 3-Hydroxy-3-Methylglutaryl-Coenzyme A Synthase

Abstract: Ceestatin therefore exerts its anti-HCV effects through inhibition of HMG-CoA synthase. It may prove useful as an antiviral agent, as a probe to study HCV replication, and as a cholesterol-lowering agent. The logical stepwise process employed to discover the mechanism of action of ceestatin can serve as a general experimental strategy to uncover the targets on which novel uncharacterized anti-HCV compounds act.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…It has been demonstrated, that Hmgcs1 possesses a prolonged expression in HCV infected humanized mice (Walters et al, 2006). Further, it has been shown that blocking the mevalonate pathway with Hmgcr inhibitors (statins) (Ye et al, 2003) or with the Hmgcs1 inhibitor ceestatin, leads to suppression of HCV replication (Delang et al, 2009;Peng et al, 2011). The siRNA-mediated knockdown of Hmgcs1 in our study had no direct effect on HCV replication; however, the Hmgcs1 knockdown has been described to suppress HCV replication in alternative HCV cell culture systems (OR6 cells and JFH1) (Peng et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated, that Hmgcs1 possesses a prolonged expression in HCV infected humanized mice (Walters et al, 2006). Further, it has been shown that blocking the mevalonate pathway with Hmgcr inhibitors (statins) (Ye et al, 2003) or with the Hmgcs1 inhibitor ceestatin, leads to suppression of HCV replication (Delang et al, 2009;Peng et al, 2011). The siRNA-mediated knockdown of Hmgcs1 in our study had no direct effect on HCV replication; however, the Hmgcs1 knockdown has been described to suppress HCV replication in alternative HCV cell culture systems (OR6 cells and JFH1) (Peng et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Further, it has been shown that blocking the mevalonate pathway with Hmgcr inhibitors (statins) (Ye et al, 2003) or with the Hmgcs1 inhibitor ceestatin, leads to suppression of HCV replication (Delang et al, 2009;Peng et al, 2011). The siRNA-mediated knockdown of Hmgcs1 in our study had no direct effect on HCV replication; however, the Hmgcs1 knockdown has been described to suppress HCV replication in alternative HCV cell culture systems (OR6 cells and JFH1) (Peng et al, 2011). Idh1, as well as the mevalonate pathway, is sterol-controlled and activated by sterol regulatory element binding proteins (Srebps) (Shechter et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Blocking the mevalonate pathway at this more proximal step has also been demonstrated to block HCV replication. 74 The role of the mevalonate pathway has been elucidated to involve the important geranylgeranylation of FBL2, a host protein, which interacts with NS5A to promote replication. 75 The Bloch pathway of cholesterol biosynthesis has also been implicated in HCV replication, but its exact function has yet to be clearly elucidated.…”
Section: Replication Is Dependent On Cholesterol and Fatty Acid Synthmentioning
confidence: 99%
“…Higher serum triglycerides, total cholesterol and LDL levels were correlated with higher HCV RNA levels [83] . Ceestatin, a novel small molecule inhibitor of hepatitis C virus replication, inhibits 3-hydroxy-3-methylglutarylcoenzyme A (HMG-CoA) reductase in a dose-dependent manner [84] . Polyunsaturated liposomes are reported to be antiviral against hepatitis B and C viruses by decreasing cholesterol levels in infected cells [85] .…”
Section: Vitamin D In Viral Hepatitismentioning
confidence: 99%